Four dominions - Lustbader, Eric (Lustbader, Eric. Testament novel., 2018)
The End of Days has been predicted for the last two thousand years, but now it is upon us. Emma and Bravo Shaw have rescued the Testament of Lucifer from nefarious hands, but despite their efforts Lucifer's Fallen have already woken, including the four thrones of legend, and their corruption reaches to the highest ranks. Even the Shaws are not immune, as Leviathan is coming, and no one is safe.